Growth of Social Entrepreneurship Through Village Owned Enterprises (BUMDes) in The Pematang Johar, Sumatera Utara Province - Bayu Andrew Tampubolon; Marlon Sihombing; R. Hamdani Harahap (PERSPEKTIF, 2023)
Social entrepreneurship is an important concept for realizing the welfare of rural communities. This concept refers to the dedication of individuals, who have the character of a leader, who actively cooperates with their community, to realize collective welfare. This study aims to analyze the Growth of Social Entrepreneurship Through Village Owned Enterprises (VOE) in Pematang Johar. This research is descriptive qualitative research. Data collection techniques used in this study were interviews, literature studies, and observation. The results of the study show that the growth of social entrepreneurship through the Pematang Johar VOE is still being carried out on a limited basis. This is due to the still uneven understanding of VOE managers regarding the concept and definition of social entrepreneurship. This has had an impact on not maximally alleviating social problems in the village of Pematang Johar. In addition, the growth of social entrepreneurship through VOE Pematang Johar is also hampered due to business management in business units that are not managed professionally by competent people.